Análise histomorfométrica do processo de reparo após o reimplante de dentes de rato mantidos em soro do leite bovino e leite integral - Corrêa, Ana Paula Simões [UNESP] (2014)
Minimal extra-alveolar dry storage period or uses of a suitable storage media are crucial to maintaining the vitality of the periodontal ligament (PDL). Whey has similar properties to milk, such a condition attracted attention for investigating its use as a storage medium. The aim of this study was to evaluate the repair process after replantation of rat teeth previously kept in whey and whole milk. To this, 36 male rats were used, under general anesthesia upper right incisor were extracted and reimplanted. Treatment was performed, dividing in four groups, of 9 animals each. Group I without any treatment the teeth were immediately reimplanted (positive control). Group II teeth were immersed in 50mL sweet whey, for 60 minutes. Group III teeth were kept for 60 minutes in 50mL long shelf-life whole milk, UHT (Parmalat ®). Group IV teeth were kept in dry for the same period (negative control). Then, animals tooth in Groups II, III and IV were reimplanted in their sockets. The animals were subjected euthanasia 60 days after replantation. The specimens were stained in Hematoxylin and eosin for histomorphometric analysis. Regarding the organization of the periodontal ligament and the extent and depth of inflammatory resorption, there was a statistically significant difference between groups I (Immediate) and IV (Late). The whey milk and whole milk showed similar results and therefore the whey can be indicated as the storage medium for avulsed teeth